1979
DOI: 10.1177/000331977903000505
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Acid and Alkaline Phosphatase Activities in the Blood Vessels of Normotensive and Hypertensive Rats

Abstract: Samples of aortae and caudal arteries from normotensive and hypertensive rats were studied for cytochemical and biochemical determinations of acid and alkaline phosphatase activities. Cytochemical examination revealed an increased amount of acid phosphatase reaction product in hypertensive samples, with extensive localization to the extracellular matrix. Alkaline phosphatase activity was localized to the plasma membrane of fibroblasts and vascular smooth muscle cells and to the extracellular matrix. Biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Previous biochemical studies have shown that subcellular membrane fractions isolated from rat aorta, mesenteric arteries, caudal arteries and mesenteric veins displayed pnitrophenyl phosphatase activity in the alka line pH range [Twietmeyer el al., 1979;Kwan et al, 1979, In small mesenteric arter ies the alkaline phosphatase activity was sub stantially higher in the muscle than in the other nonmuscular components of the blood vessels including the connective tissue and fat cells [Crane and Bury, 1966;Kwan et al, 1979], Distribution of the alkaline /?-nitrophenyl phosphatase activities determined biochemically in various subcellular mem brane fractions suggested that this enzyme is primarily associated with the smooth muscle plasma membrane of mesenteric arteries and veins , Similar findings in caudal artery using a histochemical technique have also been reported [Twietmeyer et al, 1979]. Limas and Cohn [1973] suggested that the alkaline phosphatase in canine aortic mi crosomal fraction may be related to the Ca2+-ATPase in the regulation of intracellular con centration.…”
Section: Genera! Characteristics O F Vascular Smooth Muscle Alkaline supporting
confidence: 66%
See 2 more Smart Citations
“…Previous biochemical studies have shown that subcellular membrane fractions isolated from rat aorta, mesenteric arteries, caudal arteries and mesenteric veins displayed pnitrophenyl phosphatase activity in the alka line pH range [Twietmeyer el al., 1979;Kwan et al, 1979, In small mesenteric arter ies the alkaline phosphatase activity was sub stantially higher in the muscle than in the other nonmuscular components of the blood vessels including the connective tissue and fat cells [Crane and Bury, 1966;Kwan et al, 1979], Distribution of the alkaline /?-nitrophenyl phosphatase activities determined biochemically in various subcellular mem brane fractions suggested that this enzyme is primarily associated with the smooth muscle plasma membrane of mesenteric arteries and veins , Similar findings in caudal artery using a histochemical technique have also been reported [Twietmeyer et al, 1979]. Limas and Cohn [1973] suggested that the alkaline phosphatase in canine aortic mi crosomal fraction may be related to the Ca2+-ATPase in the regulation of intracellular con centration.…”
Section: Genera! Characteristics O F Vascular Smooth Muscle Alkaline supporting
confidence: 66%
“…The distribution of alka line phosphatase in mammalian tissues or various cell types suggests that this enzyme may be involved in transport function and tissue regeneration [for a recent review, see McComb et al, 1979], Alkaline phosphatase is almost absent from skeletal muscle [Fernley, 1971], In cardiac muscle, alkaline phos phatase is more abundant in the right atrium [Muller and Pearse, 1969], The information on alkaline phosphatase in smooth muscles is quite fragmentary. For example, little alka line phosphatase activity was observed in some smooth muscles including rat myome trium [Grover et al, 1980a] as well as gastric fundus , rabbit intestine [Grover et al, 1980c] and dog trachealis [Grover et al, 1980b], whereas relatively higher alkaline phosphatase activity was ob served in rat vas deferens and some vascular smooth muscles [Twietmeyer et al, 1979;Kwan et al, 1979], The level of alkaline phosphatase activity in vas cular smooth muscles appeared to vary with the size and the type of blood vessels. Our recent studies of the subcellular membrane fractions isolated from rat mesenteric arteries [Kwan et al, 1979] and veins have shown that the distribution of alkaline phosphatase activities paralleled that of the plasma membrane marker enzyme ac tivities, including 5'-nucleotidase and phos phodiesterase 1.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, AP detection along the abluminal endothelial plasma membrane and in pericytes can hardly be reconciled with an anti-coagulant effect as its principal enzyme function in the heart. Cardiac AP is inducible by experimentally administered catecholamines (25) and by increased endogenous catecholamine associated with hypertensive disease in DOCA (26) or spontaneously hypertensive rats (27,28). On the other hand, radiation-induced cardiomyopathy is associated with reduced myocardial catecholamine production and loss of AP activity (14,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Basal Mg2+ ATPase activity which is also the high est in F, fraction of both vein and artery (data not shown), is also lower in venous plasma membrane fraction compared to arterial plasma membrane fraction (223.0 ± 27.5 versus 325.9 ± 43.9 pmol/mg/h, n = 6). Al though little is known concerning the func tional role of alkaline phosphatase [McComb et al, 1979] and basal Mg2+-ATPase in vas cular smooth muscle [Wei et al, 1976a[Wei et al, , 1976b, changes of these enzyme activities in small and large arteries have been associated with hypertensive vascular disease [Wei et al, 1976a;Twietmeyer et al, 1979;Kwan et al, 1979a].…”
Section: Comparison O F Biochemical Propertiesmentioning
confidence: 99%